Development of Sterilized Duck Meat in Coconut (Cocos nucifera) Sauce - Ebron, Maria Petra O.; Paladan, Nerisa N.; O. Ebron, Percival (Journal of Food Health and Bioenvironmental Science, 2024)
This study developed a readily available food product and utilized the Muscovy duck in thermal processing with coconut sauce, ginger, and other ingredients. Ultimately, Muscovy duck in a bottle serves as a stand-in for other high-protein foods like cheese and meat. The study used experimental and developmental research methodologies to produce the final product. According to the sensory evaluation results, the formulation that was deemed acceptable was the Muscovy duck with coconut sauce and ginger (treatment code 654), which had the highest overall acceptance score of 8.37. With a general acceptability score of 8.23 for sensory qualities, the application of the 75-min thermal treatment was deemed appropriate. The application of high temperature and pressure at a certain time eliminates the microorganisms that cause spoilage and improves the quality. The addition of coconut sauce and ginger improves the flavor of the product. However, further studies on the effect of coconut sauce and ingredients added in the cooking of the Muscovy duck meat in its nutritional component are suggested. Furthermore, to demonstrate that the product is safe and has a longer shelf life, the shelf-life analysis of the bottled Muscovy duck meat with the designated ingredients must be taken into account.